Development of Children’s Motor Ability Through The Use of Vlog Media - Nurul Islamiyah; Elok Farida (Yayasan Avicenna, 2022)
This study aims to analyze and examine the use of vlog media in developing children's motor skills. In this study, the approach used is descriptive qualitative case study type. Data collection uses observation and in-depth interviews and is supported by documentation. The research location is at RA Nurul Hidayah Kalikajar Paiton Probolinggo. Data analysis techniques used are data collection, data reduction, data presentation, and data inference. The results of the study show that vlog media used to explain motor activities such as coloring, drawing, cutting, and whispering can develop children's motor skills. Thus, children become more focused in learning, more imaginative, and easier to find children's interests. Animations and various colorful images contained in vlogs are also able to motivate children to learn. The implications of using vlog media make it easy for teachers to teach and students easily digest the material.